STUDY OF THE FORMATION OF MESOPOROUS TiO2 USING ISOPROPOXIDE PRECURSORS UNDER LESS WATER CONDITIONS - Indriana Kartini; Gao Qing Lu (Indonesian Journal of Chemistry, 2005)
The role of the synthesis parameters (the molar ratio of template, isopropyl alcohol, acetylacetone, and water with respect to titanium(IV) tetraisopropoxide) has been thoroughly investigated to understand their effects on the mesostructures and the formation of crystalline phases of mesoporous titania xerogels in less water condition (no added water) at 60 oC. The resultant mesoporous titania are more likely to have worm-hole like structure as the dominant stable structure. The template appears to play no significant role in structure directing at mesophase level. However, increasing the amount of the template delays the formation of anatase crystalline phase.